Lamniporichnus vulgaris igen. et isp. nov.: Traces of insect larvae in stone fruits of hackberry (Celtis) from the Miocene and Pleistocene of the Czech Republic - Mikulas,R.; Dvorak,Z.; Pek,I. (Journal of the Czech Geological Society, 1998)
Traces made probably by insect larvae in stone fruits of the Miocene hackberry, Celtis lacunosa, are described as Lamniporichnus vulgaris igen. et isp. nov. They were found in the opencast mine Merkur-North in the Most (North Bohemian) brown-coal basin. The newly proposed ichnogenus comprises borings in those wooden parts of fruits which contain a hollow filled with non-xylic digestible tissue (stones, nuts). The borings consist of a short cylindrical tunnel joining the stone (nut) surface and a natural hollow inside the xylic body. In comparison, the ichnogenus Carporichnus Genise, 1995 represents a longitudinal central cavity and a radial tunnel, both made by the tracemaker. Less favourably preseved material of Celtis sp. from the Pleistocene fill of karst cavities at Vitosov (Northern Moravia) provided also remains of presumably insect borings.
Keywords: Insect borings; Miocene; Pleistocene; Most Basin; karst sediments; Czech Republic